Macroeconomic determinants of corporate failures. Evidence from Romania and Spain - Anghel, Ion; Enache, Calcedonia; Merino, Fernando (Journal of Business Economics and Management, 2020)
The purpose of this study is to investigate the reaction of the insolvency rate to the various shocks in the economies of Romania and Spain through a Structural Vector Autoregressive model. Departing from quarterly data for 2008–2016, it was found that the future values of the insolvency rate are explained by the past values of the interest rate and the retail trade index, more precisely macroeconomic risk factors cost of debt and changing in demand are main responsible for the health of non-financial corporations sector. In contrast, the influence of the investment rate on insolvency rate is not predictable. In addition, both in Romania and in Spain the interest rate is the main determinant of the insolvency rate variation, beyond its own innovations, in horizons of over 2 quarters. These results were obtained under the circumstances that the analysed period was characterized by the Great Recession and its recovery. In this situation, firms faced a lesser demand as well as a tightening on the possibilities of obtaining the external funds they needed, not only to finance their expansion projects but even their daily operations. Consequently, many firms faced a negative environment that forced them to go out of the market.